2008
DOI: 10.1021/np800579x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytotoxicity of Bidesmosidic Betulin and Betulinic Acid Saponins

Abstract: The naturally occurring cytotoxic saponin 28-O-beta-d-glucopyranosylbetulinic acid 3beta-O-alpha-l-arabinopyranoside (3) was easily synthesized along with seven bidesmosidic saponins starting from the lupane-type triterpenoids betulin (1) and betulinic acid (2). As highlighted by the preliminary cytotoxicity evaluation against A549, DLD-1, MCF7, and PC-3 human cancer cell lines, the bidesmosidic betulin saponin 22a, bearing alpha-l-rhamnopyranoside moieties at both C-3 and C-28 positions, was determined to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 49 publications
4
57
0
1
Order By: Relevance
“…These positive results prompted us to investigate in depth the cytotoxic potential of glycosylated lupane triterpenes by undertaking the preparation of bidesmosides (Gauthier et al 2008).…”
Section: Glycosidation Of Triterpenoids From Outer Bark Of B Popyriferamentioning
confidence: 99%
See 1 more Smart Citation
“…These positive results prompted us to investigate in depth the cytotoxic potential of glycosylated lupane triterpenes by undertaking the preparation of bidesmosides (Gauthier et al 2008).…”
Section: Glycosidation Of Triterpenoids From Outer Bark Of B Popyriferamentioning
confidence: 99%
“…To obtain significant information about the SAR of lupane-type bidesmosides, seven other non-natural lupane bidesmosides bearing D-glucose, L-arabinose and L-rhamnose sugar moieties were also prepared starting from betulin (34) and betulinic acid (33). The syntheses were carried out by a combination of Schmidt's procedure and phase transfer conditions using fully benzoylated trichloroacetimidate and sugar bromide donors (Gauthier et al 2008). All bidesmosides were assayed against A549, DLD-1, MCF7 and PC-3 human cancer cell lines.…”
Section: Glycosidation Of Triterpenoids From Outer Bark Of B Popyriferamentioning
confidence: 99%
“…There have been sporadic reports on the structure-activity relationship, providing a possible correlation between the cytotoxic effects and certain structural features. Readers are referred to some interesting research by Gauthier et al 24,32,33 In a recent study by Liu et al, a synthetic derivative of β-hederin was evaluated for its cytotoxic properties in five human cell lines (ie, HeLa, MCF-7, HL-60, HT1080, and Hep-G2). 34 The authors reported synthesis of 13 novel triterpenoid saponins, designed as amide derivatives of the natural cytotoxic saponin, β-hederin, using a stepwise glycosylation strategy.…”
Section: Saponins As Cytotoxic Agentsmentioning
confidence: 99%
“…Similarly, Gauthier et al have evaluated the lupane-type and oleanane-type saponins from a structureactivity-relationship perspective. 24,33 Numerous human cell lines were tested, including lung carcinoma, and also normal skin fibroblasts. In the case of oleanane-type saponins, the oleanolic acid derivatives were by far the most active, while hederegenin saponins were not so active.…”
Section: Saponins As Cytotoxic Agentsmentioning
confidence: 99%
“…36 A importância do ácido betulínico (67) estimulou o desenvolvimento de novas atividades de pesquisa na busca, inclusive, de produtos derivados dotados de outras atividades biológicas através de biotransformações químicas 37 ou utilizando, inclusive, novos reagentes e novas reações. [38][39][40][41] Transformações microbiológicas (biotransformações, Esquema 6) para obtenção de substâncias mais ativas e/ou menos tóxicas assumem interesse social e econômico, principalmente quando tais conversões seletivas através de modificações sintéticas revelam dificuldades (Esquema 6). 37 As transformações microbiológicas de substâncias naturais e sintéticas oferecem novos horizontes para modificações estruturais destinadas a vários objetivos, desde a introdução de grupos funcionais a rearranjos moleculares.…”
Section: Substâncias Orgânicas Naturais Anti-hivunclassified